Ableism and Disablism in the UK Environmental Movement. (August 2017) - Fenney, Deborah
This article considers disabled people's involvement with the UK environmental movement. It draws on findings from qualitative research with disabled people in the UK exploring experiences of access to sustainable lifestyles. A number of experiences of disablism (the manifestation of oppression against disabled people) and ableism (assumptions and valorisations of non-disabled normality) were described. Similar issues were also identified in relevant documentary sources and from research into disabled people's experiences in the context of other movements such as the wider anti-capitalist movement. These findings suggest that ableism may be a significant feature of the UK environmental movement. If this is the case, there are important implications for the wider success of this movement's aims in terms of achieving environmental protection, as well as for the ongoing exclusion experienced by disabled people with regard to pro-environmental activities.